Abundant Symmetry-Breaking Solutions of the Nonlocal Alice–Bob Benjamin–Ono System. (31st May 2020) - Shen, Wang; Ma, Zheng-Yi; Fei, Jin-Xi; Zhu, Quan-Yong; Chen, Jun-Chao
Abstract : The Benjamin–Ono equation is a useful model to describe the long internal gravity waves in deep stratified fluids. In this paper, the nonlocal Alice–Bob Benjamin–Ono system is induced via the parity and time-reversal symmetry reduction. By introducing an extended Bäcklund transformation, the symmetry-breaking soliton, breather, and lump solutions for this system are obtained through the derived Hirota bilinear form. By taking suitable constants in the involved ansatz functions, abundant fascinating symmetry-breaking structures of the related explicit solutions are shown.